Aldehyde Dehydrogenase (ALDH) Activity Does Not Select for Cells with Enhanced Aggressive Properties in Malignant Melanoma - Lina Prasmickaite; Birgit Engesæter; Nirma Skrbo; Tina Hellenes; Alexandr Kristian; Nina K. Oliver; Zhenhe Suo; Gunhild M. Mælandsmo (2010)
Background Malignant melanoma is an exceptionally aggressive, drug-resistant and heterogeneous cancer. Recently it has been shown that melanoma cells with high clonogenic and tumourigenic abilities are common, but markers distinguishing such cells from cells lacking these abilities have not been identified. There is therefore no definite evidence that an exclusive cell subpopulation, i.e. cancer stem cells (CSC), exists in malignant melanoma. Rather, it is suggested that multiple cell populations are implicated in initiation and progression of the disease, making it of importance to identify subpopulations with elevated aggressive properties. Methods and Findings In several other cancer forms, Aldehyde Dehydrogenase (ALDH), which plays a role in stem cell biology and resistance, is a valuable functional marker for identification of cells that show enhanced aggressiveness and drug-resistance. Furthermore, the presence of ALDH+ cells is linked to poor clinical prognosis in these cancers. By analyzing cell cultures, xenografts and patient biopsies, we showed that aggressive melanoma harboured a large, distinguishable ALDH+ subpopulation. In vivo, ALDH+ cells gave rise to ALDH− cells, while the opposite conversion was rare, indicating a higher abilities of ALDH+ cells to reestablish tumour heterogeneity with respect to the ALDH phenotype. However, both ALDH+ and ALDH− cells demonstrated similarly high abilities for clone formation in vitro and tumour initiation in vivo. Furthermore, both subpopulations showed similar sensitivity to the anti-melanoma drugs, dacarbazine and lexatumumab. Conclusions These findings suggest that ALDH does not distinguish tumour-initiating and/or therapy-resistant cells, implying that the ALDH phenotype is not associated with more-aggressive subpopulations in malignant melanoma, and arguing against ALDH as a "universal" marker. Besides, it was shown that the ability to reestablish tumour heterogeneity is not necessarily linked to the more aggressive phenotype.